Sistem Pemberian Pakan Ikan Otomatis Berbasis IOT - Lalu Delsi Samsumar; Hambali Hambali; Zaenudin Zaenudin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Pond fish farming requires regular care and feeding of the fish. Fish feeding is usually done manually by spreading the food over the entire surface of the pond. Spreading feed manually will take a long time to feed and drain energy. It is not uncommon for owners to sometimes forget to feed the fish at the specified time. Based on these problems, the NodeMCU ESP8266-based automatic fish feeding system with blynk time setting is able to assist fish farmers in the process of feeding automatically according to the desired time. This automatic fish feeding device can act as a timer for fish feeding and the amount of food released per time is determined automatically in the Arduino ide program. This automatic fish feed has a time input which is then processed by the NodeMCU ESP8266 as a microcontroller and an internet connection (Wifi) connected to the blynk. This automatic fish feed is very useful for consumers in terms of feeding fish regularly and regularly, and most importantly to avoid forgetting or even overfeeding.